La vulneración del derecho a la vida digna de los extranjeros residentes en Ecuador - Paz Chamba, Diego Fernando (2023)
The present work studied from a critical perspective the situation of affectation of the right to a dignified life that foreigners residing in our country have suffered for years, since these people face a double problem, because when they leave their country for different circumstances, they lose rights, and when they arrive in the country of destination they risk not being able to access them. Faced with this problem, the Ecuadorian State has regulated in this context in order to protect the rights of foreigners, in this regard the Constitution in Art. 9 states that "foreigners who are in the Ecuadorian territory shall have the same rights and duties as Ecuadorians, according to the Constitution" (Constitution of the Republic of Ecuador, 2008, art. 9), which means that in Ecuador equality of rights is prioritized, in which foreigners are considered as holders of rights, and also as a group of priority attention according to Art. 40 of the same body of law. However, despite the existence of a wide range of regulations guaranteeing equal rights for foreigners, both nationally and internationally, the reality is different. Unfortunately, the situation of foreigners who decide to migrate to other countries means living in deplorable conditions, where their rights are affected in most cases, without the possibility of having a decent life, in which they can fully develop as human beings. The chapter was based on a qualitative approach, using the inductive-deductive, analytical-synthetic, dogmatic and comparative methods, as well as the techniques of bibliographic review and file review. The importance of the exercise of the right to a decent life was theoretically justified when defining human rights, since it refers to the right of all people to live in conditions that allow them to fully develop as human beings, with access to basic needs, opportunities and resources that allow them to lead a decent and satisfactory life. Additionally, the obligation of the State to adopt the necessary measures to promote equality, justice and well-being of all persons, whether Ecuadorians or foreigners, and to make effective the right to a decent life.